Acute kidney injury and mortality in critically ill children - Putri Amelia; Munar Lubis; Ema Mutiara; Yunnie Trisnawati (Indonesian Pediatric Society, 2014)
Background Mortality from acute kidney injury (AKI) can be ashigh as 60% in critically ill children. This high mortality rate isinfluenced by the severity of primary diseases, organ dysfunction,and the stage of acute kidney injury.Objective To assess for an as sedation between AKI and mortalityin critically ill children hospitalized in the pediatric intensive careunit (PICU).Methods A cross-sectional study was conducted from Aprilto July 2012. All patients aged 1 month to 18 years who werehospitalized in the PICU for more than 24 hours were included.Urine output and serum creatinine levels were evaluated daily.Patients were categorized according to the pediatric risk, injury,failure, loss, and end stage renal disease (pRIFLE) criteria. Chisquare, Fisher's exact, Mann-'hitney U, and Kruskal-Wallis testswere used to assess for an association between AKI, mortality,pediatric logistic organ dysfunction (PELOD) score, and lengthof PICU stay. AP value of < 0.05 was considered as statisticallysignificant.Results During the study period, 57 children were admitted,consisting of 25 (43.9%) females and 32 (56.1 %) males, witha median age of 43 months. The prevalance of AKI was 31.5%(18/57) and classified into stages: risk 13/18, injury 3/18, andfailure 2/18. The mortality rate for AKI was 16. 7%. There was noassociation between AKI and mortality (P=0.592). The PELODscores were found to be similar among patients (SD 11.3 2 vs. SD12.23; P=0.830), and there was no association between AKI andlength of PICU stay (P=0.819).Conclusion There is no association between AKI and mortalityin critically ill children admitted in PICU.